COMPARING THE RESULTS TREATMENT FOR MILD AND MODERATE ROSACEA BY ACID AZELAIC 10% WITH METRONIDAZOLE 1% (Vietnam Journal of Community Medicine, 2022)
Objectives: To compare the results of treatment of mild and moderate rosacea with Azelaic acid10% Metronidazole 1%.Methods: A randomized controlled intervention study on 60 patients, 30 of whom used Azlaic 10%and 30 of whom metronidazole 1%.Results: In the Azelaic group, the mean CEAS score before treatment was 9.1±3.0, after 12 weeksof treatment it decreased to 0.3±0.4. In the Metronidazole group, the mean CEAS score beforetreatment was 9.1±3.4, after 12 weeks of treatment it decreased to 1.6±0.5. In the Azelaic group, themean IGAS score before treatment was 2.2 ± 0.7, after 12 weeks of treatment it decreased to 0.07 ±0.3. The mean IGAS score in the metronidazole group before treatment was 2.1±0.7, after 12 weeksof treatment it decreased to 0.1±0.3. Before treatment, the GFSS score for assessing hot flushes wasequal between the Azelaic and Metronidazole groups, 0.7 ± 0.7. After 12 weeks of treatment, patientsin both groups were symptom free. In the Azelaic group, there were 81.2% of patients with itchingand 60% of patients with stinging. This condition was less common in the Metronidazole group with57.1% of patients with itching and 55.6% of patients with stinging.Conclusions: Azelaic 10% and Metronidazole 1% have both been shown to be effective in treatingrosacea, although Azelaic has been shown to be slightly more effective. In contrast, the frequency ofmild itching and stinging reactions was more common in the Azelaic group.
Keywords: Rosacea treatment, rosacea, Azelaic 10%, Metronidazole 1%.